Online Distance Learning and Online Learning implementation to Civil Engineering student for subject CSC128 / Azlina Mohd Mydin, Wan Anisha Wan Mohammad and Rafizah Kechil - Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha; Kechil, Rafizah (Unit Penerbitan JSKM, 2020)
Online Distance Learning (ODL) and Online Learning (OL) are the current trending in flexible education. This approach allows anyone to learn from anywhere and anytime. During this COVID-19 pandemic, all the education institutions in all around the world are suggested to conduct or run their education system using this ODL and OL approach. UiTM Cawangan Pulau Pinang also takes their part to the response to the ministry's recommendation in conducting ODL and OL teaching sessions. All the lectures in UiTM Cawangan Pulau Pinang are required to attend training that helps the preparation to conduct online classes. Variety of platforms and software were exposed during the training to enhance the lectures teaching techniques with online classes. The lecturers have to identify the student facility and requirements before they starts the online clasess.